Plasma circular RNA hsa_circ_0001445 and coronary artery disease: Performance as a biomarker. Issue 3 (30th January 2020) - Vilades, David; Martínez‐Camblor, Pablo; Ferrero‐Gregori, Andreu; Bär, Christian; Lu, Dongchao; Xiao, Ke; Vea, Àngela; Nasarre, Laura; Sanchez Vega, Jesus; Leta, Rubén; Carreras, Francesc; Thum, Thomas; et al.
Abstract: The role of circular RNAs (circRNAs) as biomarkers remains poorly characterized. Here, we investigated the performance of the circRNA hsa_circ_0001445 as a biomarker of coronary artery disease (CAD) in a real‐world clinical practice setting. Plasma hsa_circ_0001445 was measured in a study population of 200 consecutive patients with suspected stable CAD who had undergone coronary computed tomographic angiography (CTA). Multivariable logistic models were constructed combining conventional risk factors with established biomarkers and hsa_circ_0001445. Model robustness was internally validated by the bootstrap technique. Biomarker accuracy was evaluated using the C‐index. The integrated discrimination improvement (IDI) and net reclassification improvement (NRI) were also calculated. Risk groups were developed via classification tree models. The stability of plasma hsa_circ_0001445 was evaluated under different clinical conditions. hsa_circ_0001445 levels were associated with higher coronary atherosclerosis extent and severity with a 2‐fold increase across tertiles (28.4%‐50.0%). Levels of hsa_circ_0001445 were proportional to coronary atherosclerotic burden, even after comprehensive adjustment for cardiovascular risk factors, medications, and established biomarkers (fully adjusted OR = 0.432 for hsa_circ_0001445 as a continuous variable and fully adjusted OR = 0.277 for hsa_circ_0001445 as a binary variable). The classification of patients was improved with the incorporation of hsa_circ_0001445 into a base clinical model (CM) composed of conventional cardiovascular risk factors, showing an IDI of 0.047 and NRI of 0.482 for hsa_circ_0001445 as a continuous variable and an IDI of 0.056 and NRI of 0.373 for hsa_circ_0001445 as a binary variable. A trend toward higher discrimination capacity was also observed (C‐indexCM = 0.833, C‐indexCM+continuous hsa_circ_0001445 = 0.856 and C‐indexCM+binary hsa_circ_0001445 = 0.855). Detailed analysis of stability showed that hsa_circ_0001445 was present in plasma in a remarkably stable form. In vitro, hsa_circ_0001445 was downregulated in extracellular vesicles secreted by human coronary smooth muscle cells upon exposure to atherogenic conditions. In patients with suspected stable CAD referred for coronary CTA, plasma hsa_circ_0001445 improves the identification of coronary artery atherosclerosis.